Retrofitting of a Multi-Span Simply Supported Bridge into a Semi-Integral Bridge - Zhen Xu; Xiaoye Luo; Khaled Sennah; Baochun Chen; Yizhou Zhuang (Applied Sciences)
Thousands of multi-span, simply supported beam bridges with short or medium spans have been built in China. They often suffer from problems of cracks in the link slabs over piers, and the deterioration and damage of deck expansion joints at abutments. To address these problems, one approach is to retrofit them by converting the simply supported box beams into continuous structures over the piers and jointless bridges over the abutments. This paper discusses the design methodology and details for retrofitting the Jinpu Bridge in Zhangzhou, Fujian, China, from a simply supported bridge into a semi-integral bridge, in which semi-fixed dowel joints are used to connect the superstructure and the substructure, including piers and abutments. Simultaneously, the finite element software is used to calculate the internal forces and displacements of the structure. The analysis reveals an 11.1% reduction in the maximum positive moment at the midspan of the main beam in the semi-integral bridge compared to the simply supported bridge. However, the shear forces at the interior pier increase by 6.4%. According to the response spectrum analysis, the maximum longitudinal displacement of the semi-integral bridge’s main beam is 11.6 mm, reduced by 80.1% compared to the simply supported bridge under a dead load and earthquake effects. The maximum bending moment and shear force on the pier of the semi-integral bridge are 984.7 kN·m and 312.6 kN, respectively, both below their ultimate bearing capacities. The maximum displacement at the top of the pier is 7.7 mm, which is below the allowable 52.4 mm displacement. The calculated results conform to the design requirements specified by the code.